Tantangan Kepemimpinan Pastoral dalam Pelayanan Gen Z di Era Digital - Razat Simarmata; Jeffryson Sianipar; Debra Simamora; Nathaniel Grimaldy; Marlian Ronald A. Simanjuntak (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
Leadership in ministry is very important, especially in today's digital era with various target congregations in a church. Gen Z, which is the generation that dominates the population in Indonesia, is certainly of interest for the author to be able to know more about the various transformations that have occurred. The author is aware that the study of this transformation is very broad so that the challenge of pastoral leadership in the ministry of gen z in this digital era is the focus of this study. With this study, it is hoped that the author can participate in providing comprehensive information about the challenges of pastoral leadership in the ministry of gen z in the digital era, the factors that influence and how solutions can be done to face these challenges.